2014
DOI: 10.1523/jneurosci.4703-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Spinal Glucagon-Like Peptide-1 Receptors Specifically Suppresses Pain Hypersensitivity

Abstract: This study aims to identify the inhibitory role of the spinal glucagon like peptide-1 receptor (GLP-1R) signaling in pain hypersensitivity and its mechanism of action in rats and mice. First, GLP-1Rs were identified to be specifically expressed on microglial cells in the spinal dorsal horn, and profoundly upregulated after peripheral nerve injury. In addition, intrathecal GLP-1R agonists GLP-1(7-36) and exenatide potently alleviated formalin-, peripheral nerve injury-, bone cancer-, and diabetes-induced hypers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(151 citation statements)
references
References 68 publications
5
144
0
2
Order By: Relevance
“…It has been established that spinal cord microglial cells play a crucial role in neuropathic pain by releasing mediators that activate nociceptive neurons [90]. However, they can also be a source of β -END and release it in response to diverse stimuli, such as corticotrophin-releasing hormone (CRH) or noradrenaline stimulation [91], and upon glucagon-like peptide-1 (GLP-1) receptor activation [92]. Induction of β -END by a GLP-1 receptor agonist was found to be mediated by a p38 MAPK-dependent mechanism in spinal dorsal horn microglia [93].…”
Section: Pomc-derived Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that spinal cord microglial cells play a crucial role in neuropathic pain by releasing mediators that activate nociceptive neurons [90]. However, they can also be a source of β -END and release it in response to diverse stimuli, such as corticotrophin-releasing hormone (CRH) or noradrenaline stimulation [91], and upon glucagon-like peptide-1 (GLP-1) receptor activation [92]. Induction of β -END by a GLP-1 receptor agonist was found to be mediated by a p38 MAPK-dependent mechanism in spinal dorsal horn microglia [93].…”
Section: Pomc-derived Peptidesmentioning
confidence: 99%
“…Induction of β -END by a GLP-1 receptor agonist was found to be mediated by a p38 MAPK-dependent mechanism in spinal dorsal horn microglia [93]. Microglial β -END, in turn, mediates GLP-1 antinociceptive effects in pain hypersensitivity states by activating opioid receptors located on neurons [92]. In addition, β -END (and other opioid receptor ligands) may act directly on microglia, although little is known about direct effects of β -END on these cells.…”
Section: Pomc-derived Peptidesmentioning
confidence: 99%
“…In agreement with these results, we showed that female rats reduced GLP-1 hormone expression after the Zymosan injection. It was reported that GLP-1 hormone had an antinociceptive effect in formalin injected male rats [11,24]. This effect was related with the modulation of opioidergic system [25].…”
Section: Discussionmentioning
confidence: 99%
“…This process involves spinal microglia and astrocytes release of pro and anti-inflammatory mediators [10]. Hence, a recent study has shown that microglial activation has a potent antinociceptive activity by a mechanism that involves the intestinal hormone Glucagon-like peptide-1 (GLP-1) receptor [11]. The activation of GLP-1R promotes the release of anti-inflammatory Interleukin 10 and β-endorphins at the spinal circuit [11].…”
Section: Introductionmentioning
confidence: 99%
“…Streptozotosin ile diyabet oluşturulan farelerde GLP-1 analoglarının sinir azalmış sinir ileti hızı ve hipoaljeziyi azaltılırken ve nörit büyümesinin arttığı gözlenmiştir (27). Periferik sinir harabiyeti sonrasında medulla spinalisde GLP-1 reseptör sayısının arttığı da saptanmıştır (28). …”
Section: Glp-1 Ve Glp-1 Reseptör Agonsitlerinin Gıda Alımı Veunclassified